EQUILIBRIUM AND WELFARE IN UNREGULATED AIRLINE MARKETS - Panzar, John C. (American Economic Review, 1979)
This paper introduces and analyzes a monopolistically competitive model of airline markets which takes account of the product differentation effect resulting from variation in flight departure times, and the effects of flight frequency and load factor on service quality. The basic results are that (1) when the direct benefits (to consumers) of increasing flight frequency are exhausted, socially optimal choices of price and frequency result in zero profits for the industry, but (2) a noncooperative, free entry equilibrium always results in higher prices, lower load factors, and greater frequency than are socially optimal.